Faculty Attitudes towards Integrating University Students with Disabilities: Investigating the Utilization of E-Learning at the Middle East University - Doughlas , Amani Mohamed Walid (Dirasat: Educational Sciences, 2024)
Objectives: The current study seeks to examine faculty members’ perspectives on integrating university students with disabilities in the post-COVID-19 era, with a particular emphasis on e-learning. Methods: The study adopts a descriptive approach, using a questionnaire comprising (15) items. The questionnaire was administrated to a sample of (79) faculty members from the Faculty of Arts and Educational Sciences at Middle East University. Results: The findings of the study reveal positive attitudes among faculty members towards integrating university students with disabilities, reflected in an overall mean of (3.95) and high and medium scores across various items. The findings also indicate a lack of knowledge and training among faculty members to teach students with disabilities via e-learning platforms. Moreover, there are no statistically significant differences at the significance level of (a = 0.05) between the arithmetic averages of the faculty members’ attitudes towards integration based on the study variables (gender, degree, and specialization). However, a statistically significant difference was observed concerning the years of experience: faculty members with less than 3 years of experience had a more favorable attitude towards integration compared to those with 5 to 10 years or more, with a difference of (0.39). Conclusion: The study shows that faculty members exhibited positive attitudes towards integrating university students with disabilities in the post-COVID-19 era. However, they express a need for further knowledge and training to effectively deal with students’ disabilities.